Cell interactions between a nonpathogenic Fusarium oxysporum strain and root tissues of Eucalyptus viminalis - Salerno, María Isabel (2004)
Nonpathogenic isolates of Fusarium oxysporum can be successful antagonists of pathogenic forms of the same fungal species that commonly attacks crop plants. The characteristics that distinguish nonpathogenic from pathogenic forms are not well understood. In this study, the mode of root colonization of Eucalyptus viminalis seedlings by a nonpathogenic F. oxysporum strain is described at the ultrastructural level. Root systems of E. viminalis plants were inoculated with nonpathogenic F. oxysporum strain Fo47 in an in vitro model system. Changes in the occurrence of nonesterified and methyl-esterified pectins in colonized E. viminalis roots were evaluated by in situ immunolabeling using two monoclonal antibodies, JIM 5 and JIM 7. Modes of penetration and root colonization patterns in E. viminalis seedlings by the nonpathogenic fungus were similar to those described for pathogenic forms of F. oxysporum. However, root interactions differed in that the nonpathogenic fungus did not induce host tissue damage. No papilla-like appositions were observed in host cells in response to invading hyphae, which did not disrupt the host plasma membrane in many cases, suggesting that a biotrophic relationship was established. Root colonization by the nonpathogenic strain did not induce alteration in JIM 7 labeling of methyl-esterified pectin in E. viminalis cell walls, whereas nonesterified pectin was detected to a significantly greater extent in cell walls of roots colonized by the fungus. Pectin components decreased slightly only at points of hyphal contact with host cells. Because nonpathogenic strains utilize pectin in pure culture, host control over enzyme activity or production by the fungi may at least partly explain their compatible interactions with host tissues.